Gum Arabic in renal disease (GARDS Study): Clinical evidence of dietary supplementation impact on progression of renal dysfunction. (July 2021) - Khalid, Sami A.; Musa, Abdelrahman; Saeed, Amal; Elkhair Ali Ali, Nour; Abugroun, Elsir A.; Mohamed, Ghalib; Elnima, Elamin I.; Alkarib, Suaad Y.; Gbir Agib, Elsadig; Phillips, Glyn O.; Phillips, Aled O.
Graphical abstract: Highlights: Some experimental data suggest that dietary supplementation with Gum Arabic may have health benefits including improvement in renal function. There are no clinical trails in patients investigating the effect of Gum Arabic on progression of Chronic Kidney. This manuscript outlines the results of a clinical trial which demonstrates a beneficial effect of dietary supplementation in patients with progressive renal disease. Abstract: Administration of Gum Arabic (GA) was associated with an increase in estimated Glomerular filtration rate (eGFR) at three months (pre 24.64 ± 8.89 vs 26.20 ± 10.1p = 0.02). Subsequently there was no significant fall in eGFR. This translated to positive change in Δ eGFR within quarter at three months, (Δ eGFR 4.89 ml/min/year p=<0.001 vs pre) and six months (Δ eGFR 0.79 ml/min/year, p < 0.001 vs pre) compared to pre-intervention values. At 9 and 12 months although the mean Δ eGFR in quarter was negative, this rate of decline in renal function remained significantly less than prior to intervention (9 months Δ eGFR −1.27 ml/min/year, p= <0.001 vs pre, 12 months delta Δ eGFR −1.54 ml/min/year, p < 0.001 vs pre). Similarly, mean reciprocal creatinine, declined by 11% in the pre-intervention period but was no different to the pre-intervention values for the duration of intervention. In conclusion oral administration of Gum Arabic attenuates the rate of decline in renal function.